Single microfilaments mediate the early steps of microtubule bundling during preprophase band formation in onion cotyledon epidermal cells - Takeuchi, Miyuki (Mol Biol Cell, 2016)
The preprophase band (PPB) is a cytokinetic apparatus that determines the site of cell division in plants. It originates as a broad band of microtubules (MTs) in G2 and narrows to demarcate the future division site during late prophase. Studies with fluorescent probes have shown that PPBs contain F-actin during early stages of their development but become actin depleted in late prophase. Although this suggests that actins contribute to the early stages of PPB formation, how actins contribute to PPB-MT organization remains unsolved. To address this question, we used electron tomography to investigate the spatial relationship between microfilaments (MFs) and MTs at different stages of PPB assembly in onion cotyledon epidermal cells. We demonstrate that the PPB actins observed by fluorescence microscopy correspond to short, single MFs. A majority of the MFs are bound to MTs, with a subset forming MT-MF-MT bridging structures. During the later stages of PPB assembly, the MF-mediated links between MTs are displaced by MT-MT linkers as the PPB MT arrays mature into tightly packed MT bundles. On the basis of these observations, we propose that the primary function of actins during PPB formation is to mediate the initial bundling of the PPB MTs.